Growth Hormone, Nitrogen and Potassium Content in the Formulated Solid Waste from Agar Processing for Fertilizer Application - Jamal Basmal; Muhamad Luthfian Henrida; Rinta Kusumawati; Nurhayati Nurhayati (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2019)
The solid waste from agar processing industries in Indonesia is enormous. The waste contains numbers of macro and micro nutrient including growth hormone that can be a good source for plant fertilizer. Utilization of solid waste obtained from agar processing into fertilizer has been carried out by mixing with Sargassum powder, fish silage and Eucheuma cottonii pasta. Various concentrations of the solid waste (13, 19, 22 and 25%) and the Sargassum powder (0, 3, 6, 9, and 12%) were used in this study to obtain optimum nutrients in the formulated fertilizers i.e. growth hormone, total nitrogen and potassium. Growth hormone were analyzed using high-performance liquid chromatography (HPLC), while N content by Kjeldahl methods and K content analyzed according AOAC.The results showed that the optimum formulation was obtained from the combination of 25% solid waste and 0% Sargassum powder, which contained the highest growth hormones i.e. auxins (IAA) 46.75 ppm, gibberellin (GA3) 22.25 ppm, cytokinin-zeatin 18.50 ppm, and cytokinin-kinetin 61.00 ppm. While the potassium content was 0.43±0.001 ppm and the total nitrogen was 0.53± 0.06%. This result meets the requirements of the Minister of Agriculture Regulation No. 261/KPTS/SR.310/M/4/2019 regarding the requirements for total N in organic fertilizer. However, the total K+ does not meet the requirement. Therefore, enrichment with other organic raw material is still needed.